PENGARUH LARUTAN DAUN PEPAYA (Carica papaya L.) TERHADAP KUALITAS TELUR AYAM RAS - Inas Sabrina; Sari Tuswati; Sulistyaningtyas; Muhammad Hidayat (MEDIA PETERNAKAN, 2024)
The research titled The Effect of Papaya Leaf (Carica papaya L.) Solution on the Quality of Broiler Eggs was conducted from July 20 to August 10, 2024. This study aimed to determine the impact of soaking eggs in papaya leaf solution on egg weight loss, haugh unit, and pH of broiler eggs. The research utilized 60 broiler eggs. The egg soaking treatment in the papaya leaf solution was performed for one hour. Eggs were soaked in jars with three eggs per jar, and each treatment was replicated five times. The study employed an experimental method with a Completely Randomized Design (CRD) with a single factor, consisting of four treatments: P0 (1000 ml of water without papaya leaf solution), P1 (900 ml of water + 100 ml of papaya leaf solution), P2 (800 ml of water + 200 ml of papaya leaf solution), and P3 (700 ml of water + 300 ml of papaya leaf solution). Each treatment had five replications, resulting in 20 experimental units, with three eggs per unit, making a total of 60 eggs. The measured variables were egg weight loss, haugh unit, and pH of broiler eggs. The average egg weight loss with soaking in papaya leaf solution at doses of 0%, 10%, 20%, and 30% was 3.27 ± 1.86; 3.43 ± 1.94; 3.08 ± 1.80; and 3.01 ± 1.76, respectively. The average haugh unit values for eggs with soaking in papaya leaf solution at doses of 0%, 10%, 20%, and 30% were 52.46; 54.86; 58.26; and 58.13, respectively. The average pH values for eggs with soaking in papaya leaf solution at doses of 0%, 10%, 20%, and 30% were 8.94; 8.89; 8.80; and 8.55, respectively. Soaking eggs in papaya leaf solution at doses of 0%, 10%, 20%, and 30% resulted in no significant effect on egg weight loss, haugh unit, and egg pH